Diagnóstico tardío de VIH/sida en pacientes rurales dado por baja sospecha diagnostica en la comunidad médica. Reportes de caso. - Saint-Pierre-Contreras, Gustavo; Valencia-Castillo, Melissa; Conei-Valencia, Daniel (Revista Facultad de Medicina de la Universidad Nacional de Colombia)
Introduction: The prevalence of the human immunodeficiency virus (HIV) infection in Latin America has not been adequately studied, but it is estimated that in Chile half of the patients who are infected have not been diagnosed and are not controlled or receiving treatment. Case presentation: This paper presents two clinical cases of male patients aged 22 and 33, without a medical history, and with multiple consultations for different reasons in various clinical services. The diagnosis was made at the AIDS stage (acquired immunodeficiency syndrome), with the complications associated with late diagnosis. Conclusions: HIV is an underdiagnosed pathology, mostly due to lack of suspicion and prejudiced attitudes towards HIV testing. The medical staff should take responsibility for the early study of these cases to reduce the impact of the disease, especially in places where vulnerable populations live.